Genetic predispositions moderate the effectiveness of tobacco excise taxes - Eric A. W. Slob (Public Library of Science (PLoS), 2021)
Background Tobacco consumption is one of the leading causes of preventable death. In this study, we analyze whether someone’s genetic predisposition to smoking moderates the response to tobacco excise taxes. Methods We interact polygenic scores for smoking behavior with state-level tobacco excise taxes in longitudinal data (1992-2016) from the US Health and Retirement Study (N = 12,058). Results Someone’s genetic propensity to smoking moderates the effect of tobacco excise taxes on smoking behavior along the extensive margin (smoking vs. not smoking) and the intensive margin (the amount of tobacco consumed). In our analysis sample, we do not find a significant gene-environment interaction effect on smoking cessation. Conclusions When tobacco excise taxes are relatively high, those with a high genetic predisposition to smoking are less likely (i) to smoke, and (ii) to smoke heavily. While tobacco excise taxes have been effective in reducing smoking, the gene-environment interaction effects we observe in our sample suggest that policy makers could benefit from taking into account the moderating role of genes in the design of future tobacco control policies.